Ever Bumped by Dead Weight? - Dow Chemical Company (1947)
Color print advertisement for Dowmetal, a magnesium alloy manufactured and sold by the Dow Chemical Company. Depicts a downcast man sitting on his luggage while a plane departs in the background. A second image shows a man working on an airplane wing, next to which accompanying text describes how heavy luggage could affect one's airline travel. The use of magnesium to manufacture lightweight and durable airline parts allows greater passenger capacity and weight allowance. The Dowmetal logo, a hand holding a winged ingot of magnesium, is located in the bottom right of the advertisement.
Keywords: Advertising; Dow Chemical Company; Advertising, Industrial; Chemical Industry; Airplanes; Airplanes--Parts